Improving our mechanistic understanding of the indirect effects of CMV infection in transplant recipients. Issue 9 (23rd April 2019) - L'Huillier, Arnaud G.; Ferreira, Victor H.; Ku, Terrance; Bahinskaya, Ilona; Kumar, Deepali; Humar, Atul
Abstract : Cytomegalovirus (CMV) is an immunomodulatory virus that indirectly increases the risk for bacterial, fungal, and viral infections. However, the pathogenesis of this phenomenon is poorly understood. We determined whether inflammatory responses to different Toll‐like receptor (TLR) ligands are blunted during CMV infection in solid‐organ transplant (SOT) patients. Peripheral blood mononuclear cells from 38 SOT patients with and without CMV were incubated in the presence of various viral, fungal, and bacterial TLR ligands. Cytokines were measured in the supernatant by multiplex enzyme‐linked immunosorbent assay. Patients had blunted cytokine responses to bacterial, fungal, and viral ligands during CMV infection when compared to the absence of CMV infection. This was independent of viral load, clinical presentation of CMV infection or immunosuppression, supporting the clinical observation in SOT recipients that CMV infection increases susceptibility to bacterial, fungal, and other viral infections. Moreover, in the absence of CMV infection, patients with subsequent CMV infection had lower cytokines in response to TLR ligands compared to those without subsequent CMV infection, suggesting that inherent differences in patients not directly related to CMV also contribute to this increased susceptibility. In summary, these data provide novel ex vivo evidence to support indirect effects of CMV. Abstract : This study demonstrates that toll‐like receptor–mediated pathways play an important role in the indirect effects of CMV, especially increased susceptibility to other viral, bacterial, and fungal infections.